The Role Of Financial Development And Governance In Economic Growth And Environmental Sustainability: Case Of New Zealand - Souibgui, Moez (Journal of Ecohumanism, 2025)
This study examines the relationship between energy consumption, foreign direct investment (FDI), governance, and economic growth, as well as the impact of financial development, governance, and exchange rate fluctuations on CO2 emissions in New Zealand from 1992 to 2022. Using the autoregressive distributed lag (ARDL) model, the study provides empirical insights into both the short- and long-term effects of these variables. The findings indicate that both renewable and nonrenewable energy consumption contribute positively to economic growth, with FDI playing a significant role in fostering growth when supported by strong governance. However, natural resource rents have a detrimental long-term effect on economic performance, suggesting that resource dependency may hinder sustainable development. In terms of environmental impact, financial development and governance appear to reduce CO2 emissions, while nonrenewable energy consumption exacerbates pollution. The results emphasize the need for policies promoting renewable energy investment and sustainable resource management to balance economic growth and environmental sustainability. The variables in this study are time series data covering the period from 1992 to 2022. Data on CO2 emissions, and renewable and non-renewable energy consumption, sourced from the International Energy Agency (IEA). Information on GDP obtained from the national statistics database of New Zealand. The financial development and foreign direct investment data extracted from the International Monetary Fund (IMF) database, while data on governance and natural resource rents retrieved from the World Bank database.